Biocrusts do not differentially influence emergence and early establishment of native and non‐native grasses. Issue 12 (9th December 2021) - McIntyre, Cheryl; Archer, Steven R.; Predick, Katharine I.; Belnap, Jayne
Abstract: Biological soil crusts (biocrusts) cover the soil surface of global drylands and interact with vascular plants. Biocrusts may influence the availability and nature of safe sites for plant recruitment and the susceptibility of an area to invasion by non‐native species. Therefore, to investigate the potential role of biocrusts in invasive species management, we sought to determine whether native and non‐native grass recruitments in two North American deserts were differentially affected by biocrusts. We conducted a series of coordinated experiments in field, semi‐controlled, and controlled environment settings in the Colorado Plateau and Sonoran Desert using contrasting biocrust and grass functional types. Experiments in field environments focused on early establishment of grass seedlings whereas controlled environment experiments focused on seedling emergence. Within each experiment, we compared responses (frequency, magnitude, and timing of emergence/establishment) both across species (biocrust types pooled) and across species and levels of biocrust development. Native grasses varied by experiment and included Aristida purpurea, A. purpurea var. longiseta, Bouteloua gracilis, and Vulpia octoflora . Emergence of non‐native Bromus tectorum was similar to that of native grasses on the Colorado Plateau. Differences in emergence of native vs. non‐native grasses in the Sonoran Desert were species‐ and response‐specific. Emergence of the non‐native Bromus rubens was comparable to that of native grasses whereas emergence frequency and magnitude of the non‐native Pennisetum ciliare was lower compared with two of four native species. Within a grass species, emergence was higher and faster on bare soil compared with biocrusts in the Sonoran Desert semi‐controlled and greenhouse environment experiments. However, the pattern was not consistent across other experiments. When comparing across Colorado Plateau and Sonoran Desert biocrusts in greenhouse experiments, we found that emergence of native grasses was higher on Colorado Plateau biocrusts. Based on the lack of consistent results across our experiments, grass recruitment on biocrusts appears to be driven more by species‐specific traits than species provenance. Our greenhouse experiments suggest that biocrust topographic relief is an important safe site trait influencing plant recruitment.